The Gazelle's dream : game drives of the old and new worlds - Betts, A. V. G.; Van Pelt, W. Paul (Adapa monograph series., 2021)
"Once the world's prairies, grasslands, steppes and tundra teemed with massive herds of game: gazelle, wild ass, bison, caribou and antelope. Humans seeking to hunt these large fast-moving herds devised a range of specialised traps that share many characteristics across all continents. Typically consisting of guiding walls or lines of stones leading to an enclosure or trap, game drives were designed for a mass killing. Construction of the game drive, organisation of the hunt and processing of the carcass often required group co-operation and in many cases game drives have been linked to seasonal gatherings of otherwise scattered groups, who may have used these occasions not only to hunt, but also for social, ritual and economic activities. The Gazelle's Dream: Game Drives of the Old and New Worlds is the first comparative study of game drives, examining this mode of hunting across three continents and a broad range of periods. The book describes the hunting of bison in North America, reindeer in Scandinavia, antelope in Tibet and an extensive array of examples from the greater Middle East, from Egypt to Armenia. The Gazelle's Dream will be of value to anyone with an interest in the history of hunting and wildlife management"--|c Provided by publisher